Word complexity modulates the divided-word effect during Chinese reading - Zhang, Mingzhe; Bai, Xuejun; Li, Sainan (Frontiers in Psychology, 2022)
The present study further examined the influence of word complexity on the divided-word effect. By manipulating three presentation conditions (line-final presentation vs. divided-word presentation vs. line-initial presentation) and visual complexity (high vs. low), we found a significant divided-word effect that the reading times such as gaze duration and total reading time were significantly longer in the divided-word presentation condition than that in the line-final or line initial presentation condition, and the total number of fixations was greater in the divided-word presentation condition than that in the line-final or line-initial presentation condition. On the measure of total reading time, the marginally significant interaction between the divided-word versus line-final presentation comparison and complexity showed that the divided-word effect was larger for low complexity words than that for high complexity words. These results suggested that dividing a word across two lines interferes with reading, and word complexity modulates this effect.